DIALOGISMO NO DIREITO INTERNACIONAL DOS DIREITOS HUMANOS (PROPOSTA DE NOVO MONISMO): : SUPREMACIA DA NORMA MAIS FAVORÁVEL - PRINCÍPIO PRO HOMINE - Leal Silva, Gabriella (2025)
The article deals with the theoretical and practical implications of the relations between International Law and State Internal Law, seeking to establish how the effectiveness and applicability of International Law is materialized in the internal legal order of States. The study understands the Pro Homine principle (supremacy of the most favorable norm) as a central determining actor, with regard to International Human Rights Law, capable of resolving the difficulties that still circumvent these relationships. The investigation demonstrates the proposal to adopt dialogical internationalist monism as a guiding path for these relationships, enshrining a stance of compromise, coherence and dialogue between legal orders in the face of human rights. The study concludes that theoretical divergence must be ruled out, (traditional classificatory theories) favoring the primacy of the human person and, as a consequence, the applicability of instruments that privilege the dialogue of sources. Postmodernity requires that the jurist, but not just him, is better prepared to defend and protect human rights.